Synthesis, structure, Hirshfeld surface analysis and catecholase activity of Ni(II) complex with sterically constrained phenol based ligand - Mandal, Bikramaditya (2021)
A mononuclear square planar Ni(II) complex [NiᴵᴵL] (1) with sterically encumbered phenol based tetra dentate N₂O2₂ ligand has been synthesized. Several spectroscopic tools have been employed to characterize this complex. The crystal structure of this Ni(II) complex obtained from single crystal X-ray diffraction study reveals that the central metal ion adopts a square planar environment and crystalized in monoclinic space group C 2/c with a = 24.1784 (10), b = 9.3537 (4) and c = 8.3326 (4) with β = 97.0690 (11). The Hirshfeld surface analysis shows halogen-halogen interaction. The Ni(II) complex has been found to be an effective catalyst for the aerial oxidation of 3,5-DTBC to 3,5- DTBQ in methanol. For kinetic study, Michaelis-Menten model has been approached to determine the Kcₐₜ, Kₘ and Vₘₐₓ. The kinetic studies confirm that the turnover number (TON) of complex 1 is 1.762 × 10³ h⁻¹.